Diasporic Identity in the Face of Trauma — Diasporic Identity and the Second World War Trauma in Kerri Sakamoto’s “The Electrical Field” (1998) - Antoniak, Joanna (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2021)
DIASPORIC IDENTITY IN THE FACE OF TRAUMA — DIASPORIC IDENTITY AND THE SECOND WORLD WAR TRAUMA IN KERRI SAKAMOTO’S THE ELECTRICAL FIELD (1998) The Electrical Field is the debut novel of Kerri Sakamoto, a Canadian novelist of Japanese descent. The novel deals with the effects, aftermath, and consequences of the internment of Japanese Canadians during the Second World War. Set in the 1970s, the story presented in the novel is told by Asako Saito, a middle-aged woman living with her bedridden father and younger brother on the outskirts of Toronto. The starting point of the novel is the murder of Saito’s friend, Chisako, and her hakujin lover, Mr Spears, and the subsequent disappearance of Yano, Chisako’s husband, and their two children, Kimi and Tam. These two events not only disrupt the peaceful existence of the small community, but also trigger the influx of memories from the internment camp which soon overwhelms Saito, blurring the boundaries between the past and the present. The aim of this article is to discuss how Sakamoto’s novel depicts the complexity of the impact of internment trauma not only on those Japanese Canadians who were directly affected by it, but also on the next generation. Using the combination of trauma theory — especially the notions of collective and transgenerational trauma — and historical data about the Japanese diaspora in Canada before, during and after the Second World War, the author will discuss the impact of the internment trauma on the diasporic identities of the members of three Japanese Canadian families portrayed in the novel. DIASPORYCZNA TOŻSAMOŚĆ W OBLICZU TRAUMY — TOŻSAMOŚĆ DIASPORYCZNA I TRAUMA DRUGIEJ WOJNY ŚWIATOWEJ W THE ELECTRICAL FIELD (1998) KERRI SAKAMOTO The Electrical Field to debiutancka powieść Kerri Sakamoto, kanadyjskiej pisarki o japońskich korzeniach. Powieść opisuje efekty i konsekwencje internowania Kanadyjczyków japońskiego pochodzenia w czasie drugiej wojny światowej. Osadzona w latach 70. XX stulecia historia opowiedziana jest z perspektywy Asako Saito, kobiety w średnim wieku mieszkającej na obrzeżach Toronto ze swoim przykutym do łóżka ojcem i młodszym bratem. Spokojne życie Asako i jej rodziny zostaje zburzone, gdy kobieta dowiaduje się, że jej przyjaciółka Chisako została zamordowana wraz ze swoim białym kochankiem, panem Spearsem, a jej mąż, Yano, i dwójka ich dzieci zaginęła. Wydarzenia te nie tylko wstrząsają spokojną społecznością, ale również przywołują wspomnienia z okresu internowania, które przytłaczają Asako, zacierając granicę pomiędzy przeszłością i teraźniejszością. Celem artykułu jest omówienie sposobu, w jaki Sakamoto przedstawia wpływ traumy nie tylko na tych Kanadyjczyków japońskiego pochodzenia, którzy byli internowani, ale również na kolejne pokolenia. Posługując się teorią traumy — odwołując się zwłaszcza do konceptów traumy zbiorowej i transpokoleniowej — i danych historycznych na temat sytuacji japońskiej diaspory w Kanadzie przed, w czasie i po drugiej wojnie światowej, autorka omawia wpływ traumy na tożsamości diasporyczne członków trzech japońsko-kanadyjskich rodzin przedstawionych w powieści.